2022
DOI: 10.1613/jair.1.12802
|View full text |Cite
|
Sign up to set email alerts
|

CASA: Conversational Aspect Sentiment Analysis for Dialogue Understanding

Abstract: Dialogue understanding has always been a bottleneck for many conversational tasks, such as dialogue response generation and conversational question answering. To expedite the progress in this area, we introduce the task of conversational aspect sentiment analysis (CASA) that can provide useful fine-grained sentiment information for dialogue understanding and planning. Overall, this task extends the standard aspect-based sentiment analysis to the conversational scenario with several major adaptations. To aid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…7 Dialogue-level quadruple analysis Song et al (2022) introduced a new task called conversational aspect sentiment analysis (CASA), which aims to provide fine-grained sentiment information for dialogue understanding and planning.…”
Section: Summary Of the Best Methods For Each Approachmentioning
confidence: 99%
“…7 Dialogue-level quadruple analysis Song et al (2022) introduced a new task called conversational aspect sentiment analysis (CASA), which aims to provide fine-grained sentiment information for dialogue understanding and planning.…”
Section: Summary Of the Best Methods For Each Approachmentioning
confidence: 99%
“…In recent years, effective dialogue agents have explored various knowledge for facilitating dialogue understanding and response generation, such as sentiment (Song et al, 2022), speaker emotion (Poria et al, 2019), discourse structure (Wang et al, 2021a(Wang et al, , 2023a, and external knowledge from different knowledge sources. This work falls into the last category of the above research lines, which has shown effectiveness in alleviating the hallucination problem.…”
Section: Knowledge-aided Dialogue Modelmentioning
confidence: 99%
“…Dialogue systems have attracted increasing attention from both academia and industry researches (Chen et al, 2017;Deriu et al, 2021;Gao et al, 2021a). The tasks can be commonly divided into two categories: task-oriented dialogue systems (Wen et al, 2017;Dinan et al, 2019;Mehri et al, 2020) and chit-chat dialogue systems (Ritter et al, 2011;Li et al, 2017;Cui et al, 2020;Song et al, 2022). The former aims to interact in the context of a specific task, while the latter chats with users without task and domain restrictions.…”
Section: Introductionmentioning
confidence: 99%